2015
DOI: 10.1016/j.biocon.2015.06.029
|View full text |Cite
|
Sign up to set email alerts
|

A riparian conservation network for ecological resilience

Abstract: a b s t r a c t a r t i c l e i n f oA crucial gap exists between the static nature of the United States' existing protected areas and the dynamic impacts of 21st century stressors, such as habitat loss and fragmentation and climate change. Connectivity is a valuable element for bridging that gap and building the ecological resilience of existing protected areas. However, creating terrestrial connectivity by designing individual migration corridors across fragmented landscapes is arguably untenable at a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 46 publications
1
45
0
2
Order By: Relevance
“…Resiliency functions and services include flood storage, buffering of storm damage, protecting water quality by filtering pollutants and sediment out of runoff generated by severe storm events, groundwater recharge and provision of water supply during drought, provision of wildlife refuges and corridors and maintenance of biodiversity (Junk et al 2013; Association of State Wetland Managers 2015a; Narayan et al 2016), regulating microclimate (Zhang et al 2016) and physically buffering coasts from sea level rise and increases in storm surges (Millennium Ecosystem Assessment 2005), as well as others enumerated elsewhere in this article. Anderson et al (2016a) state, BProtecting wetlands and riparian corridors has been suggested as one of the single best actions in promoting resilience and in sustaining biodiversity (Naiman et al 1993, Fremier et al 2015)^.…”
Section: Part 2: Emerging Policies and Management Strategies For Protmentioning
confidence: 99%
“…Resiliency functions and services include flood storage, buffering of storm damage, protecting water quality by filtering pollutants and sediment out of runoff generated by severe storm events, groundwater recharge and provision of water supply during drought, provision of wildlife refuges and corridors and maintenance of biodiversity (Junk et al 2013; Association of State Wetland Managers 2015a; Narayan et al 2016), regulating microclimate (Zhang et al 2016) and physically buffering coasts from sea level rise and increases in storm surges (Millennium Ecosystem Assessment 2005), as well as others enumerated elsewhere in this article. Anderson et al (2016a) state, BProtecting wetlands and riparian corridors has been suggested as one of the single best actions in promoting resilience and in sustaining biodiversity (Naiman et al 1993, Fremier et al 2015)^.…”
Section: Part 2: Emerging Policies and Management Strategies For Protmentioning
confidence: 99%
“…Specifically, we hypothesized that detection probability would be influenced by factors associated predation risk (Lesmeister et al , Thorne et al ), seasonal changes in food availability (Hackett et al ), the use of different scent‐based attractants (Schlexer ), and the monitoring station setup (Kays and Slauson ). We hypothesized that occupancy probability would be influenced by topographic features that relate to efficient movement (Fremier et al ), the availability of warmer habitats during the winter to reduce thermoregulatory stress (Lesmeister et al ), and predation risk (Lesmeister et al , Thorne et al ).…”
mentioning
confidence: 99%
“…These forests shelter not only specialized species that live in riparian areas, but also species of adjacent habitats, being important corridors for the dispersal of animals and plants at the landscape level [3][4][5]. Therefore, deforestation and degradation of riparian forests result in severe loss of biodiversity and ecosystem functions [2,6,7].…”
Section: Introductionmentioning
confidence: 99%